Physical planning factors the long term development plan of Sto. Nino School - Santaromana, Francis L. 1960- (Quezon City College of Architecture, University of the Philippines, Diliman, 1992)
This study attepmts to consider all the physical planning factors affecting the long range development plan for a secondary level school. it amis to provide the theoretical frameworks, methodologies, scope and limitations, guidelines, assumptions, initial requirements, directives, format, character and design considerations that are to be pursued for the eventual phyical implementation as an actual project.
Thesis (Master of Architecture : Architectural Design)--University of the Philippines, Diliman.
Keywords: Schools -- Designs and plans; School planning